Mycobacterium tuberculosis SIT42 Infection in an Abused Dog in Southern Italy - Vangone, Lucia; Cardillo, Lorena; Riccardi, Marita Georgia; Borriello, Giorgia; Cerrone, Anna; Coppa, Paolo; Scialla, Roberto; Sannino, Emanuela; Miletti, Gianluca; Galiero, Giorgio; Fusco, Giovanna (Frontiers in Veterinary Science, 2021)
A case of Mycobacterium tuberculosis infection is described in a dead adult male dog in Southern Italy. The carcass was found by the Health Authority in a gypsy encampment. It was admitted to our forensic veterinary medicine unit, with a suspicion of cruelty to the animal. Necropsy showed beating and traumatism signs, and mistreating was confirmed. Gross lesions included multiple nodular hepatic lesions, hemorrhagic enteritis with enlarged mesenteric lymph nodes, body cavity effusions, and an adrenal neoplasm. Bacteriological and molecular analyses were carried out on the liver lesions that enabled to identify M. tuberculosis SIT42 (LAM9). Drug-resistance patterns were evaluated by screening mutations on the rpoB and katG genes that showed susceptibility to both rifampin and isoniazid, respectively. Very few studies report canine tuberculosis, and little is known about the disease in Italy. To the authors' knowledge, this is the first report of Mycobacterium tuberculosis SIT42 infection in a dog in Italy.